The Link between NAFLD and Colorectal Cancer: Insights from Liver Function Enzymes and Serum Biomarkers in a Case-Control Study - Yasir H. Sabah; Firas Hassan (مجلة مركز بحوث التقنيات الاحيائية)
Background: Colorectal cancer (CRC) is a major killer, and nonalcoholic fatty liver disease (NAFLD) affects almost one-quarter of the global population. The aim of the study is to Investigate the correlation between nonalcoholic fatty liver disease (NAFLD) and an increased risk of colorectal cancer (CRC), as well as the relationship between liver function enzymes and specific serum biomarkers in CRC patients with NAFLD. Methods: A case-control study involving 60 participants was conducted from February to August 2022. The patients with colon cancer were examined at Baghdad Medical City's Al-Amal Hospital for Radiation and Nuclear Medicine and Oncology Teaching Hospital, and blood samples were taken. Thirty patients with NAFLD who had just been diagnosed with colorectal cancer (CRC) were recruited. The study included 30 healthy individuals who served as controls. Colorimetric method kits were used to determine liver function enzymes. Also, the serum biomarkers cathepsin B, Obestatin, and kininogen-1 were calculated by ELISA. The serum levels of liver function enzymes, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were evaluated in newly diagnosed CRC patients who suffered NAFLD and compared with healthy controls. Results: It was indicated that all tested enzymes were significantly elevated in newly diagnosed CRC patients with NAFLD. The correlation was conducted between liver function enzymes and biological markers. In the patient group, positive correlations were detected between ALT and cathepsin-B, obestatin, and kininogen-1 (r = 0.43, 0.66, and 0.52, respectively), with a significance in correlation recorded with obestatin and kininogen-1 (p = 0.007 and 0.047, respectively). AST inversely (negatively) correlated with cathepsin-B, obestatin, and kininogen-1, with no significance in control. However, in the patient group, the correlation was shifted to be positive with no significance.   In the control group, ALP positively correlated with cathepsin-B, obestatin, and kininogen-1 (r = 0.1, 0.33, and 0.57, respectively). No significant differences were recorded between ALP, cathepsin-B, and obestatin. Meanwhile, the positive correlation between ALP and kininogen-1 was significant (p = 0.026).  This study found significant liver function enzyme increases in newly diagnosed colorectal cancer (CRC) individuals with NAFLD. Selected blood biomarkers and liver function enzymes were positively correlated in CRC patients with NAFLD. These data suggest that NAFLD may raise the risk of colorectal cancer, which could inform future studies and clinical practice.